BRAIN IMAGING OF PSYCHOPATHY: A NARRATIVE LITERATURE REVIEW - Angkawidjaja, Katharina Merry Apriliani; Suryadinata, Rivan Virlando (Jurnal Biosains Pascasarjana, 2024)
The general definition of psychopathic is an individual who focuses on self-perspective, is feelingless, without compassion, lacks empathy, lacks/disloyalty, and lacks the ability to form close relationships (less intimacy). Psychopathy is also known as psychopathic, antisocial, disocial, and sociopathic personality disorder. In Indonesia, clinical diagnosis guidelines for psychopathic individuals still refer to Dissocial Personality Disorder according to the Guidelines for Classification and Diagnosis of Mental Disorders Edition III (PPDGJ-III), coupled with other commonly used supporting examinations, namely the MMPI (Minnesota Multiphasic Personality Inventory), LSRP (Levensone Self-Report Psychopathy Scales), PCL:SV (Psychopathy Checklist: Screening Version). This Narrative Literature Review aims to summarize findings about brain imaging in Psychopath. As for psychopathic-related brain imaging, namely aberrant brain activity was found in the prefrontal area, temporal cortex, limbic (amygdala- hippocampus complex), striatum, corpus callosum, and insular. These findings hope to be able to explain the basic etiological of deviant behavior in psychopathic perpetrators. Thus, psychopathic neuroanatomy is a research area that has the potential to contribute as a preventive and curative measure of psychopathy on a scientific basis.